2018
DOI: 10.1021/acs.energyfuels.7b03940
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Assisted Stabilization of Lifted Non-premixed Jet Flames

Abstract: The present study experimentally investigates the effects of plasma discharges on the stabilization of lifted non-premixed jet flames in a stream of co-flow air. The plasma discharge is produced on the sharp edge of the fuel nozzle exit, facilitating its impact on flame stabilization. It is observed that the application of plasma discharges has an impact on the enhancement of flame lift-off velocity, lift-off height, and hysteresis phenomenon and leads to plasma-attached flames, plasma-enhanced lifted flames, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Recently, research on stabilization of ammonia flame through plasma has also been conducted [90]. This is a usual method for flame stabilization that has been performed for a long time [91][92][93][94][95][96]. However, in this study, it was experimentally demonstrated that flame stabilization and NOx generation could be simultaneously reduced through plasma-assisted combustion.…”
Section: Oxygen Enrichment and Plasma Application For Ammonia-flame Enhancementmentioning
confidence: 89%
“…Recently, research on stabilization of ammonia flame through plasma has also been conducted [90]. This is a usual method for flame stabilization that has been performed for a long time [91][92][93][94][95][96]. However, in this study, it was experimentally demonstrated that flame stabilization and NOx generation could be simultaneously reduced through plasma-assisted combustion.…”
Section: Oxygen Enrichment and Plasma Application For Ammonia-flame Enhancementmentioning
confidence: 89%
“…It should be noted that although most flames in industrial combustors are turbulent, 28 the research should start from laminar conditions. This is for the purpose of avoiding influence from turbulent fluctuation and capturing more accurately the burning information.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…Nonequilibrium plasma has the characteristics of low overall temperature, high utilization of discharge energy, and an obvious activation effect, which can generate a large number of active atoms and groups. Experiments in a continuous-flow combustion reactor had shown that the nonequilibrium plasma generated by continuous discharge could expand the lean burn limit and enhance flame stability. Therefore, nonequilibrium plasma has significant advantages in stabilizing combustion and improving mixture activity.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments in a continuous-flow combustion reactor had shown that the nonequilibrium plasma generated by continuous discharge could expand the lean burn limit and enhance flame stability. 18 20 Therefore, nonequilibrium plasma has significant advantages in stabilizing combustion and improving mixture activity.…”
Section: Introductionmentioning
confidence: 99%